Kinetic modeling of Candida shehatae ATCC 22984 on xylose and glucose for ethanol production - Prawphan Yuvadetkun (2018)
© 2017 Taylor & Francis. Candida shehatae ATCC 22984, a xylose-fermenting yeast, showed an ability to produce ethanol in both glucose and xylose medium. Maximum ethanol produced by the yeast was 48.8 g/L in xylose and 52.6 g/L in glucose medium with ethanol yields that varied between 0.3 and 0.4 g/g depended on initial sugar concentrations. Xylitol was a coproduct of ethanol production using xylose as substrate, and glycerol was detected in both glucose and xylose media. Kinetic model equations indicated that growth, substrate consumption, and product formation of C. shehatae were governed by substrate limitation and inhibition by ethanol. The model suggested that cell growth was totally inhibited at 40 g/L of ethanol and ethanol production capacity of the yeast was 52 g/L, which were in good agreement with experimental results. The developed model could be used to explain C. shehatae fermentation in glucose and xylose media from 20 to 170 g/L sugar concentrations.